2022
DOI: 10.1021/acsami.2c00448
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Self-Assembly with NIR Light-Activated Cascade Effect for Improving Local Treatment on Solid Tumors

Abstract: Incomplete local treatment of solid tumors is the main cause of tumor difficult to cure, and easily leads to tumor metastasis and recurrence. The dense external matrix and hypoxic microenvironment of solid tumors severely restrict the therapy efficacy of local tumors. Enhancing the infiltration ability of agents to tumor tissues and adapting the therapy mode favored to hypoxic microenvironments are beneficial to improve the cure rate of tumors. In this work, we designed and developed a self-assembled biomateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Additionally, Zhou et al. 16 reported that using PLGA–PEG–poly(N‐isopropylacrylamide) and PEG–PLGA–biotin to deliver photochemical agent (ATT‐2), forming PATA nanoparticles, facilitated effective tumor targeting and the property of phase transition temperature. Moreover, PLGA nanoparticles can be also modified by target peptide to enhance cancer therapy or by codelivery with magnetic nanoparticles for increasing T 2 contrast magnetic resonance imaging (MRI).…”
Section: Backbones and Structures Of Multifunctional Nanoparticlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, Zhou et al. 16 reported that using PLGA–PEG–poly(N‐isopropylacrylamide) and PEG–PLGA–biotin to deliver photochemical agent (ATT‐2), forming PATA nanoparticles, facilitated effective tumor targeting and the property of phase transition temperature. Moreover, PLGA nanoparticles can be also modified by target peptide to enhance cancer therapy or by codelivery with magnetic nanoparticles for increasing T 2 contrast magnetic resonance imaging (MRI).…”
Section: Backbones and Structures Of Multifunctional Nanoparticlesmentioning
confidence: 99%
“…PLGA-PEGmaleimide was loaded with IR780 and then conjugated with PD-L1 binding peptide; as a result, aNP@IR780 showed a strong CT26 antitumor effect by activating immune cells following near-infrared irradiation (NIR). Additionally, Zhou et al 16 reported that using PLGA-PEGpoly(N-isopropylacrylamide) and PEG-PLGA-biotin to deliver photochemical agent (ATT-2), forming PATA nanoparticles, facilitated effective tumor targeting and the property of phase transition temperature. Moreover, PLGA nanoparticles can be also modified by target peptide to enhance cancer therapy or by codelivery with magnetic nanoparticles for increasing T 2 contrast magnetic resonance imaging (MRI).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations